Wheat rhizosphere fungal community is affected by tillage and plant growth - Li, Yüze; Wang, Ziting; Li, Tong; Zhao, Deqiang; Han, Juan; Liao, Yuncheng (Agriculture, ecosystems & environment, 2021)
Agricultural management measures, including tillage, considerably alter the rhizosphere fungal community; however, traditional snapshot sampling fail to represent the rhizosphere fungal community patterns over time. Here, we conducted a continuous study of wheat rhizosphere fungal communities through long-term tillage experiments (consisting of conventional and conservation tillage) to clarify tillage and growth stage effects. Tillage practices always affected rhizosphere fungal communities (R2 = 18%), and these effects significantly differed between plant growth stages. Drastic changes in plant phenotypes during the growing season may have driven the changes in rhizosphere fungal communities. Specifically, in the tillering stage (the early period of wheat growth), plant traits dynamics and the abundance of two crop-tillage sensitive modules were highly correlated. The conservation tillage abundant module was mainly composed of saprotrophs, whereas pathogens constituted the majority in modules enriched by conventional tillage. These results indicate that it is possible to influence the rhizosphere fungal community structure and function through agricultural management mediated by plant growth. Manipulation of tillage-sensitive OTUs and early rhizosphere fungal community modules can provide new opportunities for developing sustainable and highly productive agroecosystems. •How rhizosphere fungi respond to tillage and crop growth remain unknown.•Crop growth can severely affect the rhizosphere fungal community.•Specific species and modules in the networks can significantly respond to tillage.